THE DYNAMIC OF DIALECT VARIATION IN LANGUAGE LEARNING - Febriyanti Sunaryo, Dera; Nuryanti, Febriani; Nurchasanah, Titik; Hasti Varisca, Zennia (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
This research was conducted to see the dynamic of dialects variation in learning languages. As it is common, Indonesian people tend to communicate using dialects in the society. In this case, it has its own challenges where the dialect of the language that everyone speaks allows them not to come from the region, but because of their influence on the daily communication. Using a qualitative approach. The preparation of this journal uses a descriptive method through literature or literature research. This means reviewing and analyzing books, documents, and scientific journals that have been published. Language indicates a person's cultural and social identity in addition to functioning as a means of communication. Over the past few decades, research has shown that the social environment can greatly influence a person's language development, especially during childhood. There are several related environments such as family roles, peer and environmental influences, media and technology influences, multilingual and multicultural influences, and education.